Personality Profiles of Victims of Intimate Partner Violence and Inmates: Contributions of the Personality Assessment Inventory and the Minnesota Multiphasic Personality Inventory-2-Restructured Form - Mauro Paulino; Mariana Moniz; Octávio Moura; Daniel Rijo; Rosa F. Novo; Mário R. Simões (Social Sciences)
Although there is a growing body of research focused on the personality characteristics of victims and offenders, only a few studies have investigated both groups through robust and comprehensive measures of personality. The present study aimed to compare the PAI and MMPI-2-RF profiles between victims and offenders and investigate the influence of adverse childhood experiences (ACEs) on their results. Samples of 107 female victims (age: M = 42.71; SD = 11.25) and 154 male inmates (age: M = 36.51; SD = 12.72) were compared, and statistically significant differences were found on several PAI and MMPI-2-RF scales. While the victims tended to score higher on scales such as Anxiety, Stress, Somatic Complaints and Thought Dysfunction, the inmates scored higher on scales related to Antisocial Traits, Drug Problems, and Aggressiveness-Revised, among others. Both groups reported a large number of ACEs, and linear regression analyses revealed that ACEs predicted PAI and MMPI-2-RF scores. A discriminant analysis also found that specific ACEs accurately discriminate psychological characteristics between victim and offender groups. In conclusion, the PAI and the MMPI-2-RF provided valuable information on the characteristics of victims and inmates, contributing to a better understanding of the nature of victimization and crime perpetration.